Application of Pulse Radiolysis to Mechanistic Investigations of Water Oxidation Catalysis. Issue 4 (18th September 2013) - Polyansky, Dmitry E.; Hurst, James K.; Lymar, Sergei V.
Abstract: Radiolysis is a powerful technique capable of generating both inorganic and organic strong one‐electron oxidants over a wide range of aqueous medium conditions. Accordingly, current pulse radiolysis methods are quite advanced and have been productively used to study dynamics of many types of redox reactions for several decades. Nonetheless, despite its apparent usefulness for gaining mechanistic insights into water oxidation catalysis through probing normally inaccessible oxidation states of the catalysts, pulse radiolysis has only infrequently been applied to this purpose. In this paper, we identify those oxidizing radicals deemed most suited to these types of studies and describe methods for their radiolytic generation, review the scant literature on pulse radiolysis studies of both heterogeneous and homogeneous water oxidation catalysts, and discuss results of our own investigations of two dimeric and one monomeric ruthenium‐based catalysts, each of which appears to oxidize water by a distinct pathway. The optical spectra and redox dynamics of transient species determined have in each case provided information central to evaluating proposed catalytic mechanisms. Moreover, quantitative "over‐oxidation" by generating a stoichiometric excess amount of radicals has permitted investigation of an intermediate formed from a highly reactive precursor, demonstrating the unique capability of the pulse radiolysis method. As illustrated by these examples, this technique is broadly applicable to investigations of catalyzed water oxidation, which has the potential to become a method of choice for detecting and characterizing reaction transients. Abstract : The ability of pulse radiolysis to generate strong one‐electron oxidants makes it a powerful tool for mechanistic studies of water oxidation catalysis. This assertion is documented by a review of its application to studies of both heterogeneous and homogeneous catalysts from which the optical spectra and redox dynamics of key catalytic intermediates have been determined.